The effects of additives on the pelletization of raw and torrefied food waste - Ruwaida, Abdul Rasid; Elamparithy, G.; Mazni, Ismail; Noorlisa, Harun (Universiti Malaysia Pahang, 2021)
This study evaluates the effect of various binders on the pelletization of raw and torrefied food waste (FW) towards its physical properties, including density, moisture reabsorption, and tensile strength of the formed pellets. Three binders; starch, lignin, and vegetable oil, were used to make the raw and torrefied FW pellets. It was found that the addition of lignin helps to improve the density of both, raw and torrefied FW pellets by 40% for raw FW pellets and up to 27% improvement for the torrefied FW pellets. In addition, increasing the concentration of lignin may also reduce moisture reabsorption from 48% to 40% of raw FW pellets, and the sorption was further reduced for the torrefied FW pellets. The addition of lignin improves the tensile strength, mainly the torrefied FW pellets. Results show that lignin inclusion demonstrates significant enhancement to the physical properties of FW pellets.